Schistosome AMPK Is Required for Larval Viability and Regulates Glycogen Metabolism in Adult Parasites - Hunter, Kasandra S.; Miller, André; Mentink-Kane, Margaret; Davies, Stephen J. (Frontiers in Microbiology, 2021)
On entering the mammalian host, schistosomes transition from a freshwater environment where resources are scarce, to an environment where there is an unlimited supply of glucose, their preferred energy substrate. Adult schistosome glycolytic activity consumes almost five times the parasite’s dry weight in glucose per day to meet the parasite’s energy demands, and the schistosome glycolytic enzymes and mechanisms for glucose uptake that sustain this metabolic activity have previously been identified. However, little is known of the parasite processes that regulate schistosome glucose metabolism. We previously described the Schistosoma mansoni ortholog of 5’ AMP-Activated Protein Kinase (AMPK), which is a central regulator of energy metabolism in eukaryotes, and characterized the developmental regulation of its expression and activity in S. mansoni. Here we sought to explore the function of AMPK in schistosomes and test whether it regulates parasite glycolysis. Adult schistosomes mounted a compensatory response to chemical inhibition of AMPK α, resulting in increased AMPK α protein abundance and activity. RNAi inhibition of AMPK α expression, however, suggests that AMPK α is not required for adult schistosome viability in vitro. Larval schistosomula, on the other hand, are sensitive to chemical AMPK α inhibition, and this correlates with inactivity of the AMPK α gene in this life cycle stage that precludes a compensatory response to AMPK inhibition. While our data indicate that AMPK is not essential in adult schistosomes, our results suggest that AMPK regulates adult worm glycogen stores, influencing both glycogen utilization and synthesis. AMPK may therefore play a role in the ability of adult schistosomes to survive in vivo stressors such as transient glucose deprivation and oxidative stress. These findings suggest that AMPK warrants further investigation as a potential drug target, especially for interventions aimed at preventing establishment of a schistosome infection.